Inactivation of PLK4-STIL Module Prevents Self-Renewal and Triggers p53-Dependent Differentiation in Human Pluripotent Stem Cells - Renzova, Tereza; Bohaciakova, Dasa; Esner, Milan; Pospisilova, Veronika; Barta, Tomas; Hampl, Ales; Cajanek, Lukas (Stem cell reports, 2018)
Centrioles account for centrosomes and cilia formation. Recently, a link between centrosomal components and human developmental disorders has been established. However, the exact mechanisms how centrosome abnormalities influence embryogenesis and cell fate are not understood. PLK4-STIL module represents a key element of centrosome duplication cycle. We analyzed consequences of inactivation of the module for early events of embryogenesis in human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs). We demonstrate that blocking of PLK4 or STIL functions leads to centrosome loss followed by both p53-dependent and -independent defects, including prolonged cell divisions, upregulation of p53, chromosome instability, and, importantly, reduction of pluripotency markers and induction of differentiation. We show that the observed loss of key stem cells properties is connected to alterations in mitotic timing and protein turnover. In sum, our data define a link between centrosome, its regulators, and the control of pluripotency and differentiation in PSCs.
Keywords: Mitosis; lidé; Cell Proliferation; mitóza; centrozom; Induced Pluripotent Stem Cells; pluripotency; indukované pluripotentní kmenové buňky; Centrosome; Humans; acentrosomal; Cell Self Renewal; cell cycle; centriole; protein-serin-threoninkinasy; self-renewal; buněčná diferenciace; proliferace buněk; centrosome; buněčná sebeobnova; intracelulární signální peptidy a proteiny; differentiation; stem cell; Tumor Suppressor Protein p53; nádorový supresorový protein p53; Intracellular Signaling Peptides and Proteins; Cell Differentiation; Protein Serine-Threonine Kinases